A Survey on the Impact of Energy and Buildings Sustainability Initiatives in University Campuses - Amaral, Ana R. (2019)
University campuses are complex structures, generally consisting in large amounts of built-up area and of users involved in a diversity of activities, resulting in a substantial consumption of resources, waste generation and greenhouse gases emissions, similarly to an urban community. Acting on the use phase, the so-called operations, offers the possibility of improving the environmental performance of buildings, facilities and outdoor spaces, resulting in higher savings rates at a short and medium term. Sustainability initiatives on campus operations may be arranged in several key areas, such as Energy, Buildings, Waste, Water, Transportation, Air and Climate and Food. This work focus on Energy and Buildings initiatives, by reviewing those studied or effectively implemented in university campuses with reported results in scientific publications. Literature shows a wide range and diversity of results. This work intends, thus, to understand those results, by exploring the extent to which the success of initiatives is related to campuses characteristics, particularly to the campuses dimension. The results of this work show a tendency for smaller campuses to present better results on the feasibility of actions, through higher rates of energy consumption decrease; larger ones present diverse impacts, being their probability of success dependent on the addition of supporting measures to the energy generation, as the implementation of energy storage or microgrids. These findings, even recognizing the need of more research to produce more robust conclusions, can help to identify key points for actions to optimize the adoption of sustainable strategies according to each campus specificities, and to succeed in the accomplishment of the sustainable campus principle.